2020
DOI: 10.1002/aenm.201903652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrinsic Defects of Carbon Materials on the Sodium Storage Performance

Abstract: Due to their high conductivity and low cost, carbon materials have attracted great attention in the field of energy storage, especially as anode material for sodium ion batteries. Current research focuses on introducing external defects through heteroatom engineering to improve the sodium storage performance of carbon materials. However, there is still a lack of systematic investigation of the effects of intrinsic defects prevalent in carbon materials on sodium storage performance. Herein, template‐assisted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 60 publications
5
159
0
Order By: Relevance
“…[47][48][49] This phenomenon is well in agreement with previous work. [50] The nitrogen adsorption-desorption isotherm in Figure 1e shows the samples obtained at different temperatures are close to I type. [51,52] At higher pressures, hysteresis rings of the materials can be observed, indicating the presence of a porous structure.…”
Section: Resultsmentioning
confidence: 86%
“…[47][48][49] This phenomenon is well in agreement with previous work. [50] The nitrogen adsorption-desorption isotherm in Figure 1e shows the samples obtained at different temperatures are close to I type. [51,52] At higher pressures, hysteresis rings of the materials can be observed, indicating the presence of a porous structure.…”
Section: Resultsmentioning
confidence: 86%
“…Recent studies on carbon materials have demonstrated the intrinsic coupling between the microstructure and sodium storage performance. [72][73][74][75][76][77][78] Hence, considering the greatly enhanced Na + ions adsorption capability in defect-rich carbon material, a distinct sodium storage behavior based on adsorption mechanism is expected for MAT engineered CNs material. We have shown that by using CNs as anode materials for sodium-ion battery, we can achieve high capacity and good cycle life in CNs-4 sample with expanded interlayer spacing and hierarchical porous structure (see details in Figure S39, Supporting Information).…”
Section: Ni/co/cu Metal Atom Intercalation Induced Expansion Of Graphmentioning
confidence: 99%
“…In most cases, the changes in distortion or loss of atoms in the crystal lattice of carbon hosts easily cause intrinsic defects, which can modulate their electronic structure and surface properties. [93] The intrinsic carbon defects lead to the more exposed active sites on the surface of carbon, which can mitigate the undesired LiPSs shuttle for increasing the sulfur utilization. [94] For instance, Wang et al have proposed the porous disorder carbon nanotubes as a host material for encapsulating sulfur, which can improve the cyclability and CE of LiÀ S battery.…”
Section: Sulfur Cathodementioning
confidence: 99%